Subjective Global Nutritional Assessment: Applicability in children and adolescents with malignant tumors - Nemetz, Kellen Benites; Bastos Domingues, Laura de Carvalho; Gregianin, Lauro José; da Cruz, Luciane Beitler (Clinical and Biomedical Research, 2021)
Introduction: This study investigated the applicability of the Subjective Global Nutritional Assessment (SGNA) tool to evaluate the nutritional status of pediatric cancer patients. Methods: This was a multicenter, observational cohort study of infants, children, and adolescents diagnosed with malignant tumors. Participants were evaluated at the moment they were diagnosed with a malignant tumor (EV1) and at the third month of treatment (EV2). Objective data were collected and the SGNA questionnaire was applied. Correlation between the methods was performed using the Kendall test. Results: We evaluated 216 patients at EV1 and 172 patients at EV2. During EV1, 7% of patients presented with some degree of malnutrition, according to objective measures, and 35.7% according to the SGNA. During EV2, they presented 6.4% and 26.8%, respectively. The SGNA showed ability to diagnose more malnutrition than objective indicators and the agreement found between both methods was moderate and weak. We observed a significant correlation between the SGNA and the nutritional indicators (p = <0.002), thus proving its efficacy in assessing nutritional status. Conclusion: The SGNA was applicable for evaluating the nutritional status of children and adolescents diagnosed with malignant tumors, and effective in tracking malnutrition prevalence when compared to objective nutritional assessment methods.